Knowledge and practices in community regarding antibiotic usage - Jain, Amit; Dhir, Shashi Kant; Batta, Meenal; Singh, Gaganpreet (International Journal of Research in Medical Sciences, 2016)
Background: One of the major causes of concern in medical world is rapid development of antibiotic resistance. World Health Organisation started an initiative in 2011 with a policy designed to curb this danger of antibiotic resistance. This study was designed to know the knowledge, attitude and belief of community regarding antibiotic use so that data can be generated in this region for the proper designing and implementation of awareness campaigns for the community. Methods: A single point cross sectional study was conducted in 1500 adults attending the Out Patient Department of a tertiary care hospital in Northern India. The tool used for the study was a predesigned questionnaire. The data was evaluated using descriptive statistical analysis. Results: In our study 92.8% participants admitted of having used an antibiotic at any time in their lifetime. The most common reason for use of antibiotics was common cold (36.2%). The most common antibiotic used by the participants was amoxycillin. The most common source of information regarding antibiotics and their use (63.2%) was physicians. 78.6% of the participants believed that they have awareness about rational use of antibiotics. 68.6% respondents were of the view that antibiotics are effective against both viral and bacterial infections. 52.3% of the participants believed antibiotics are not safe to use. Conclusions: The existence of a significant gap between practice of antibiotic usage and knowledge about their usage was found prevalently in the community. After noting the results of this study it is believed that there is a dire necessity to take steps to curb the menace of rapid development of resistance to antibiotics.